Functional Integration and Performance Optimization of Semiconductor Chips and Integrated Circuits in Smart Electronic Devices - Zou, Siluo (International Journal of Materials Science and Technology Studies, 2026)
In order to clarify the functional integration modes and performance optimization directions of semiconductor chips and integrated circuits in smart electronic devices, this paper combines the 2024-2025 measured industrial data of the semiconductor industry to sort out the development history of chip integration technologies, analyze the practical roles of SoC (System on Chip) and Chiplet architectures in functional integration, explore the improvement effects of low-power design, advanced packaging and new materials on chip performance, and summarize the design concepts for the collaborative optimization of chip functionality and performance. Research indicates that by 2025, high-end advanced packaging has become the core technical support for heterogeneous chip integration; the shipment volume of advanced-process high-end SoCs for smartphones continues to rise. Chiplet and high-density interconnect (HDI) technologies can effectively improve the functional integration density of chips, and relevant technological innovations have continuously broken through the performance limitations of traditional silicon-based processes. The optimization strategies summarized in this paper based on practical industrial applications can provide feasible practical references for the design and performance upgrading of chips used in smart electronic devices.